Development Of Ethnophysics-Based Teaching Materials To Improve The Self-Regulatory Skills Of Prospective Physics Teachers - Habibi Habibi; Lovy Herayanti; Baiq Azmi Sukroyanti (Postgraduate, University of Mataram, 2023)
This development research aims to produce a product in the form of an ethnophysics-based learning tool to improve prospective physics teachers' valid and effective self-regulation. The products developed are Lecture Event Units known as SAP, Student Worksheets or LKM, Teaching Materials, and test instruments. The research design used is a 4D model consisting of Defining, Designing, Developing, and Disseminating. Data collection techniques use validation sheets and evaluation tools. Device validity data was analyzed using a Likert scale. Three expert validators assess product validity. Assessment by validators with valid to very valid criteria. The effectiveness of the teaching materials developed by researchers can be determined by increasing students' self-regulation based on the results of the N-Gain test after being given a pretest and posttest. The planning indicators show that the percentage of students who were suitable/suitable before implementing the ethno-physics learning model was 42%. This indicates that more than 50% of students have self-management related to learning planning that still needs to be improved. Applying the ethno-physics learning model as a stimulus to help students manage good learning planning contributed 36%, increasing to 78%. The monitoring indicator also has the same increase in the number of students as the planning indicator, namely 36%. This can be described as more and more students being able to manage their learning by monitoring their learning process. The evaluation indicator shows the largest percentage increase in the number of students, namely 38%, while it is only 28% for strengthening. This indicates that the ethno-physics learning model has the greatest contribution to stimulating students' evaluation abilities